Wind energy assessment as a source of power generation in Bangladesh - Mondal, Mithun; Didane, Djamal Hissein; Ali, Alhadj Hisseine Issaka; Manshoor, Bukhari (Penerbit Akademia Baru, 2022)
Wind energy has been considered one of the most popular forms of renewable energy. It has been widely considered for the generation of electricity for its low maintenance cost and negligible effect on environmental pollution. The purpose of this research is to evaluate and compare the wind energy potential in seven different districts of Bangladesh including Barisal, Chittagong, Dhaka , Khulna, Rajshahi, Rangpur, and Sylhet. Data had been recorded on daily basis for the consecutive five years from 2015 until 2 019 and analysed using Weibull distribution function various essential parameters such as wind speed, wind energy density and wind power density. Results show that the monthly average wind speed varies between 0.5 m/s to 2.10 m/s for all the divisions except Chittagong where it is in the range between 3 m/s and 4.5 m/s. Similarly, the maximum wind power density and wind energy density were also found in the Chittagong division with annual densities that range between 51.86967 W/